Guideline documents on caesarean section on maternal request in Sweden: varying usability with a restrictive approach - Magdalena Mattebo; Inger K Holmström; Anna T Höglund; Mio Fredriksson (BMC Health Services Research, 2023)
Abstract Background Globally, studies illustrate different approaches among health care professionals to decision making about caesarean section (CS) and that attitudes regarding the extent to which a CS on maternal request (CSMR) can be granted vary significantly, both between professionals and countries. Absence of proper regulatory frameworks is one potential explanation for high CSMR rates in some countries, but overall, it is unclear how recommendations and guidelines on CSMR relate to CSMR rates. In Sweden, CSMR rates are low by international comparison, but statistics show that the extent to which maternity clinics perform CSMR vary among Sweden’s 21 self-governing regions. These regions are responsible for funding and delivery of healthcare, while national guidelines provide guidance for the professions throughout the country; however, they are not mandatory. To further understand considerations for CSMR requests and existing practice variations, the aim was to analyse guideline documents on CSMR at all local maternity clinics in Sweden. Methods All 43 maternity clinics in Sweden were contacted and asked for any guideline documents regarding CSMR. All clinics replied, enabling a total investigation. We used a combined deductive and inductive design, using the framework method for the analysis of qualitative data in multi-disciplinary health research. Results Overall, 32 maternity clinics reported guideline documents and 11 denied having any. Among those reporting no guideline documents, one referred to using national guideline document. Based on the Framework method, four theme categories were identified: CSMR is treated as a matter of fear of birth (FOB); How important factors are weighted in the decision-making is unclear; Birth contracts are offered in some regions; and The post-partum care is related to FOB rather than CSMR. Conclusion In order to offer women who request CS equal and just care, there is a pressing need to either implement current national guideline document at all maternity clinics or rewrite the guideline documents to enable clinics to adopt a structured approach. The emphasis must be placed on exploring the reasons behind the request and providing unbiased information and support. Our results contribute to the ongoing discussion about CSMR and lay a foundation for further research in which professionals, as well as stakeholders and both women planning pregnancy and pregnant women, can give their views on this issue.